Oral Infection Caused by Stenotrophomonas maltophilia: A Rare Presentation of an Emerging Opportunistic Pathogen. (29th January 2020) - Prates, Marcelo; Fernandes, Fernando; Proença, Francisco; Mussá, Yashad; Tavares, Ana; Pereira, André
Abstract : Stenotrophomonas maltophilia is an emerging multidrug-resistant opportunistic pathogen with an increasing incidence of nosocomial and community-acquired infection cases, mainly in immunocompromised individuals. Oral cavity infections are rare. To learn more about this infection, a case of oral cavity infection caused by S. maltophilia in an immunosuppressed patient under ventilatory therapy has been presented. The patient presented with multiple nonpainful erosive lesions of the tongue, palate, and oral mucosa. A smear of the oral lesions was performed that revealed the presence of S. maltophilia and Candida albicans, and the patient was treated with fluconazole and sulfamethoxazole associated with trimethoprim in accordance with the antimicrobial susceptibility testing. After 14 days of antibiotic therapy, there were almost no signs of the previous lesions.